Direct simulation and experimental study of zigzag maneuver of KCS in shallow water. (15th January 2016) - Carrica, Pablo M.; Mofidi, Alireza; Eloot, Katrien; Delefortrie, Guillaume
Abstract: The KCS container ship on a zigzag maneuver in shallow water is studied experimentally and numerically. The approach conditions are Fr =0.095 and H / T =1.2. Experiments were performed in the shallow water towing tank at Flanders Hydraulics Research for the workshop on verification and validation of ship maneuvering simulation methods (SIMMAN, 2014 ). CFD simulations were initially performed blind at the nominal rudder rate of 16.8°/s using direct discretization of moving rudder and propeller, including the tank bottom but neglecting walls. Grid studies were conducted for self-propulsion and the zigzag maneuver at the nominal rudder rate using grids of up to 71.3 million points. A simulation was then executed on the medium grid at the actual rudder experimental rate achieved (8.35°/s), and results analyzed. The grid study suggests that forces, moments and motions can be well predicted with coarser grids, and that medium grid results are very close to the fine grid, but flow details do not converge for the levels of refinement used. The verification results in large grid uncertainties, even though time evolutions of different variables show good grid convergence. CFD predictions match satisfactorily the experimental results for most variables, but under-predict yaw and yaw rate. Graphical abstract: Highlights: EFD and CFD of KCS zig-zag maneuver in shallow water are presented. CFD uses moving rudder and propeller with overset grids. Verification analyses were performed for self-propulsion and zigzag. CFD and EFD agree well, some CFD underprediction of overshoots and yaw rates.